IDENTIFIKASI TINGKAT KERAWANAN DEGRADASI KAWASAN HUTAN MANGROVE DESA MUARA, TANGERANG, BANTEN - Hadisti Nur Aini; Omo Rusdiana; Sri Mulatsih (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2015)
This study is intended to estimate the vulnerability of degradation of mangrove forest in Muara Village, Tangerang, Banten. There are five species of mangroves found in mangrove forest of Muara, which are: Avicennia alba, Avicennia officinnalis. Rhizophora apiculata, Rhizophora stylosa, and Rhizophora mucronata. The results showed that the mangrove forest in Muara has a high vulnerability of degradation based on the three vegetation characteristics, such as: density, domination, and biodiversity of mangrove species. The density of mangrove vegetation has only reached 739 individual/Ha. While the biodiversity of mangrove species is low and the domination level of mangrove species is high, in which the dominant species is Rhizophora mucronata. Mangrove rehabilitation activities are required by revegetation methods, and the mangrove species that are used in revegetation process are local species which available in the mangrove forest of Muara. Mangrove rehabilitation process that needs to be done is by revegetation of mangroves and mangrove species conservation. Mangrove species which is suitable for mangrove rehabilitation in Muara Village are Rhizophora mucronata and Avecinnea alba. Keywords: mangrove, forest, degradation, rehabilitation